STRUKTUR BIAYA USAHA BUDIDAYA LEBAH MADU DI DESA KUAPAN KECAMATAN TAMBANG KABUPATEN KAMPAR (Kasus Usaha Madu “Mekar Sari”) - Ilma Satriana Dewi (UIR Press, 2022)
Communities in the Riau area have started cultivating honey bees both traditionally and in a modern way. However, the development of honey bee farming (Apis cerana) is currently still not progressing even though the business has been running for quite a long time. This could have been caused by several things, namely poor business management, starting from cultivation activities to quite high production costs. This study aims to analyze breeder characteristics and profiles, analyze production costs, production, income, and business efficiency, and analyze the cost structure of the